Geoarchaeology and Castlescapes: Heritage Management Case Studies in Spain and the Eastern Baltic. (3rd July 2019) - Banerjea, Rowena Y.; Ruiz, Guillermo García-Contreras; Kalniņš, Gundars; Karczewski, Maciej; Pluskowski, Aleks; Valk, Heiki; Brown, Alexander D.
ABSTRACT: This paper promotes the application of geoarchaeology—joint studies using historical, archaeological and heritage approaches—to the conservation and management practice of castles and landscapes in the context of 'castlescapes'. Using case studies from recent research on medieval castles in frontier regions of the eastern Baltic and Spain, it demonstrates how geoarchaeology can create synergies between on-site and off-site environments and between cultural and natural heritage and draw valuable information from soils and sediments about the changing form and function of spaces within castles, and about the links between these spaces and activities in their hinterlands. Geoarchaeological approaches can also illuminate the diachronic biographies that hide from visitors in the buried archaeology of castles, which to most visitors would be blank cavasses, but which can provide snap-shots of castle life in the context of a wider landscape. Castles are commonly publicly recognised as being important historical monuments, but from a heritage perspective they are often presented in isolation from their associated historical territories, and often (especially in frontier regions) appropriated within modern politics, which has influenced both heritage management decisions and research frameworks.